Pengaruh Kualitas Produk dan Direct Marketing terhadap Keputusan Pembelian Air Minum Ziva Ro di Desa Banjarwati Kecamatan Paciran Kabupaten Lamongan - Moch Noer Arief; Sutopo; muhyidin (Al-Muzdahir : Jurnal Ekonomi Syariah, 2020)
The community in Paciran sub-district is 102,548 people. Paciran sub-district also includes industrial districts, both home industries and large industries. The need for clean water is increasing, especially those who live in areas adjacent to large factories such as in the Paciran sub-district, so that the water content is polluted by wastes from these large industries, so that the water quality in the Paciran area is especially unfit for consumption. directly because it depends on the very high TDS and PH substances. This shows that ZIVA RO drinking water is an important instrument for one of the drinking water industries in the Paciran area that uses a reverse osmosis process. This is what makes product quality and direct marketing influencing purchasing decisions. From this background, the problems obtained are: first, how is the influence of product quality on ZIVA RO drinking water decisions in Banjarwati Village, Paciran District, Lamongan Regency, second, how is the influence of direct marketing on ZIVA RO drinking water purchasing decisions in Banjarwati Village, Paciran District, Regency Lamongan. The type of research used is quantitative research, the sampling technique used is the independent sampling technique, with the number of respondents as many as 100 people, the data analysis technique used is using reliability and validity tests, correlation analysis tests, coefficients of determination, multiple linear regression analysis and , hypothesis testing. The results showed that the product quality variable did not have a significant positive effect on purchasing decisions of -0.697 > 1.984 with a significant level of t less than 0.05, namely 0.487> 005. Direct marketing from the results of this study direct marketing has no significant effect on purchasing decisions obtained by 1.091 > 1.984. With tingakat t less than 0.05 that is 0.278> 0.005.